Determinants of Frozen Food Purchase Intentions : Insights from a Developing Country - Saleem, Muhammad Abid; Wasaya, Allah; Zahra, Sadaf (Indian Journal of Marketing, 2017)
This study highlighted the role of knowledge about frozen foods and focused on what traits will change consumers’ intentions toward frozen food purchases. Further, it analysed how consumer attitudes toward frozen food acted as a mediator and family structure acted as a moderator in the relationships between knowledge of frozen food products, change seeking traits, and frozen food purchase intentions. Data was collected through a questionnaire based on adopted scales, and the sample consisted of 279 frozen food customers of branded and non-branded stores in Multan District, Pakistan. Exploratory factor analysis, confirmatory factor analysis, and multi-group moderation were conducted to provide statistical evidence for hypotheses. Knowledge about frozen foods and change seeking traits were found significant in predicting frozen food purchase intentions directly and through mediation. Additionally, family structure was found to be a significant moderator of the hypothesized path between attitude towards frozen food and frozen food purchase intentions. This study is the only one of its kind and helps to demystify frozen food purchase behaviour of consumers in a developing country like Pakistan, especially, in light of a changing social phenomenon, that is, shifting of joint family systems to nuclear family structures.